2015
DOI: 10.2147/opth.s86812
|View full text |Cite
|
Sign up to set email alerts
|

Ocular pain and discomfort after advanced surface ablation: an ignored complaint

Abstract: PurposeLaser vision correction is one of the most commonly performed elective surgical procedures in ophthalmology. Generally, discomfort besides pain (photophobia, burning sensation, tearing, and foreign body sensation) after these procedures is not taken into consideration in the clinical practice. The objective is to provide data on these symptoms and their relevance after advanced surface ablation (ASA).MethodsSingle-center survey study based on a structured questionnaire relative to the patients’ perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Postoperative discomfort or pain is still considered a bothersome side effect of PRK and a deterrent Nepafenac Ophthalmic Solution 0.3% for PRK/Kontadakis et al for performing the procedure to numerous patients. [5][6][7] Some patients who are not ideal candidates for LASIK postpone PRK due to the fear of postoperative pain. Methods to relieve postoperative pain include different techniques of epithelium removal, such as LASEK, epi-LASIK, phototherapeutic keratectomy, use of chilled balance salt solution postoperatively, bandage contact lenses and topical medication, and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative discomfort or pain is still considered a bothersome side effect of PRK and a deterrent Nepafenac Ophthalmic Solution 0.3% for PRK/Kontadakis et al for performing the procedure to numerous patients. [5][6][7] Some patients who are not ideal candidates for LASIK postpone PRK due to the fear of postoperative pain. Methods to relieve postoperative pain include different techniques of epithelium removal, such as LASEK, epi-LASIK, phototherapeutic keratectomy, use of chilled balance salt solution postoperatively, bandage contact lenses and topical medication, and NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous questionnaire developed by Sobas et al,10 the presence and intensity of the following ocular symptoms were recorded: photophobia, burning sensation, tearing, foreign body, itching, and headache. The intensity of each item was rated on a Likert scale of 4 points (range 0–3, where 0 corresponded to no symptom and 3 to the worst imaginable symptom) 11.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size was based on our previously published study in which 97% had postoperative pain 10 Subsequent to that study, clinical records suggested that 99% of patients had postoperative pain after ASA (unpublished data). Thus, we assumed that 98% of the participants would have ocular pain.…”
Section: Methodsmentioning
confidence: 99%
“…Other eye comorbidities have been described in cases of advanced surface ablation during laser refractive surgery that manifested themselves in the postoperative period with signs and symptoms such as burning/foreign body sensation, tearing, pain, and photophobia. As a consequence of this, instauration of a precise analgesic protocol has been recently suggested for patients subjected to these procedures [ 11 ].…”
Section: Ocular Comorbid Conditionsmentioning
confidence: 99%